2022
DOI: 10.3389/fcvm.2022.911845
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolomic characterization of atrial fibrillation

Abstract: BackgroundUsing human humoral metabolomic profiling, we can discover the diagnostic biomarkers and pathogenesis of disease. The specific characterization of atrial fibrillation (AF) subtypes with metabolomics may facilitate effective and targeted treatment, especially in early stages.ObjectivesBy investigating disturbed metabolic pathways, we could evaluate the diagnostic value of biomarkers based on metabolomics for different types of AF.MethodsA cohort of 363 patients was enrolled and divided into a discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…In addition to the polyamine metabolites, the results with carnitines have been most consistent, suggesting a protective role against the onset of AF. 67 , 69–71 Carnitines are an essential part of the cardiomyocyte energy metabolism, transporting fatty acids for use in mitochondrial energy production, while preventing ROS formation. 72 There is also evidence for their cardioprotective abilities, blood pressure benefit, and reduction in left ventricle dilation after an acute myocardial infarction.…”
Section: Metabolic End-products and Afmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the polyamine metabolites, the results with carnitines have been most consistent, suggesting a protective role against the onset of AF. 67 , 69–71 Carnitines are an essential part of the cardiomyocyte energy metabolism, transporting fatty acids for use in mitochondrial energy production, while preventing ROS formation. 72 There is also evidence for their cardioprotective abilities, blood pressure benefit, and reduction in left ventricle dilation after an acute myocardial infarction.…”
Section: Metabolic End-products and Afmentioning
confidence: 99%
“…In addition, several lysophosphatidylcholines (LysoPC) and cholesterol esters have been linked to AF in many recent studies. 69 , 77 , 78 , 80 , 81 LysoPC species are antiatherogenic, have anti-inflammatory responses, and reduce metabolic syndrome progression, 82 and the concentrations of these metabolites have been lower in AF patients than in controls. 81 , 82 There is also evidence on the connection between other inflammatory biomarkers and AF.…”
Section: Metabolic End-products and Afmentioning
confidence: 99%
“…A study has focused on characterizing the specific and precise metabolic features of atrial fibrillation subtypes, indicated that small-molecule metabolites may facilitate effective treatment. 603 Additionally with the use of untargeted metabolomics, a study demonstrated serum biomarkers of progression of diabetic retinopathy in Asians, and there were 171 metabolic features including glutamine, N-acetyl-l-glutamate, glutamate, aspartate, N-acetyl-l-aspartate, docosahexaenoic, icosapentaenoic, and dihomo-gamma-linolenate distinguished proliferative diabetic retinopathy patients from T2DM patients. 604 Enrichment pathway analyses for major metabolite biomarkers indicated arginine biosynthesis metabolism, d-glutamine and d-glutamate metabolism were dysregulated in advanced stages of diabetic retinopathy.…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
“…Alternatively, biomarkers obtained non-invasively from serum or other secretions, such as saliva or urine, can prove to be an invaluable tool to predict incident AF and/or prognosticate AF progression. There has been a tremendous effort to identify various biomarkers specific to AF, including serum microRNAs, other non-coding RNAs [ 112 , 113 ], proteins/hormones [ 114 , 115 ], and metabolites [ 116 , 117 ]. However, the accuracy of these biomarkers is not yet sufficient for day-to-day clinical usage.…”
Section: Perspective On Future Areas Of Researchmentioning
confidence: 99%